Effect of NAM on Nasal Symmetry and Proportions in Patients with UCLP: A Systematic Review - Puspita Sari, Felicia; Samsarga, Gede Wara; Satrio, Kenny; Putra Johansyah, Theodorus Kevin; Jonathan, Jeremy; Andhika Yogiswara, Made Dwi (Lingkar Studi Bedah Plastik Foundation, 2022)
Introduction : Nasal reconstruction presents a challenge in case of patients with unilateral cleft lip and palate (UCLP). Correction of the nasal deformity to achieve a symmetrical nose from the deficient columella and malformed nasal cartilage in cleft patients presents a great challenge. Nasoalveolar molding (NAM) was developed as a neoadjuvant therapy for patients with cleft lip and palate to improve nasal deformity before surgical intervention. The aim of this systematic review was to understand more about the effect of NAM on nasal symmetry and proportions in patients with UCLP. Method : We searched for manuscripts involving patients with UCLP who received NAM prior to cleft lip repair. Electronic literature searching of the PubMed, Scopus, Cochrane and Google scholar databases was conducted for the studies that had been published up to December 2021. Result : Presurgical NAM demonstrated benefits in nasolabial form when compared with patients who did not receive any presurgical infant orthopaedic appliances (PSIO). The use of presurgical NAM helps to achieve favourable reshaping of the nose and decrease the severity of the initial cleft deformity, resulting in improvement on nasolabial form. These changes lead to improved nasal symmetry and proportions in UCLP patients. Conclusion: The preponderance of evidence in this review suggests that presurgical NAM is a beneficial adjuvant therapy for nasal deformity correction and helps achieve nasal symmetry in patients with UCLP. However, there is insufficient evidence to conclude whether presurgical NAM produces these benefits at the time of nasal maturity.